Pelatihan Fun Physical Fitness Training untuk Guru PJOK di Bojonegoro - Sapto Wibowo; Heryanto Nur Muhammad; Nanik Indahwati; Taufiq Hidayat (Jurnal Berkarya Pengabdian Masyarakat, 2021)
Fun Physical Fitness Training is a fun and effective program of physical activity which can be applied by physical education teachers for students during the teaching-learning process. An activity-based education program that stimulates students to exercise and expects students' minds and bodies to be in better results. In this program, students are encouraged to jump, pull, hold their body, walk, jogging in the prepared place. The focus of methods and activities in Pengabdian Kepada Masyarakat (PKM), mentoring and assistance to the partners on Fun Physical Fitness Training with a circuit training method based on individual performance and not competition. Mentoring is carried out regarding the selection of movements and media used, guidance in carrying out body movements in each post with the aim of making students more fit and learning to change activity behavior by setting and achieving personal goals. This program is easily run by teachers in the physical education field of study in schools. Based on the training given to the partners, the results are: 1) they are able to identify physical fitness movement models, 2) they are able to compile a movement with a circuit model, 3) they are able to carry out movement activities based on a post by post on the circuit model, and 4) they are able to make reports on fun physical fitness training for students.